Evolução neocenozoica do relevo no oeste de Minas Gerais: compreensões a partir do Alto rio Paranaíba - Daniel Machado Facury (2024)
The evolution of the relief over time is greatly influenced by the action of the drainage network, given its erosive and constructive potential, especially in humid tropics. Records of ancient fluvial depositional levels have been prospected, organized, systematized, and interpreted to understand landscape changes, especially in the Quaternary. In Brazil, these studies have focused mainly on the Paraná River basin. Even though being a tributary of this river, the Paranaíba River has not received the same attention so far, with no studies systematizing sedimentary records in its basin. This study fills this gap and seeks, in general, to investigate the neocenozoic evolution of the Alto Paranaíba relief and its determinants through morphological organization, characteristics of the drainage network, and surface formations, with emphasis on fluvial archives. It also aimed to relate relief evolution elements with possible lithostructural, neotectonic, and climatic conditioning factors. To achieve this goal, field and office procedures were carried out. These procedures involved the application of morphometric indices, development of geomorphological compartmentalization, identification of drainage anomalies, mapping of structural lineaments, surveying, characterization, and organization of fluvial archives and other surface formations, and the collection of fluvial sediment samples for absolute dating using the Optically Stimulated Luminescence (OSL) technique. The spatial scope used consists of the Paranaíba River basin up to its confluence with the Espírito Santo River, including the basin of this watercourse. Important sedimentary cover testimonies were surveyed, such as alluvial fan deposits, and older ferruginous crusts, probably of plio-pleistocene age, representing records of past erosive cycles in the study area. Furthermore, the analyses conducted allowed the identification of three zones with distinct characteristics of their Quaternary fluvial archives. The Paranaíba River Valley zone and the zone of Tributaries of the Left Bank of the Paranaíba River and Lower Espírito Santo gather up to two ancient depositional levels, with N3 being the oldest, with ages around 9,000 years. The most recent levels form the current valley bottom. The deposits have a restricted spatial distribution and little facies diversity. The valleys in these zones are marked by great asymmetry, indicating the importance of regional tilting processes in relief evolution. The other zone, identified as Middle Espírito Santo River, presents depositional levels concentrated in the valley bottom, forming extensive terrace-plain systems. The N2, the oldest, dates to ~12,000 years, indicating some preservation in the valley bottom throughout the Holocene. This preservation is associated with previous events of drainage network rearrangements that filled the valley bottom in question, promoting armoring of the riverbed. This event appears to be associated with the reactivation of ancient faults and post-Last Glacial Maximum climate changes. The present study demonstrated the relevance of river deposits for the reconstruction of geomorphological events even in the context of mountainous areas near drainage headwaters.